Guía narrativa de fotografía y fotoperiodismo en la formación académica de los estudiantes de la carrera de Comunicación de la UNL - Chuquimarca Lima, Jordy Salvador (2024)
The quick development of Web 5.0 has changed photojournalism and photography through immediacy. Nowadays, National University of Loja's communication students' ability to fully and thoughtfully acquire photographic and photojournalistic expertise is conditioned by the overproduction of photographs. This research study focuses on the creation of a narrative guide that addresses photography and photojournalism from a critical, didactic, and visual way for the academic training of UNL communication major students. Other specific objectives were proposed to achieve this objective such as, determining whether the overproduction of images conditions the full learning of photographic and photojournalistic knowledge in UNL communication students and aligning practices on photography applied to photojournalism in contemporary times. The research study began with a bibliographic review that served as the main basis for the critical-theoretical structure on photography and photojournalism; it is important to mention that it used a mixed methodology, including expert interviews, teacher surveys of 77 students majoring in communication, and participant observation by the researcher in both in-person and online classroom settings. The variables included training quality, instructors' and students' perceptions, real-world application, and resource availability. Instant photo sharing is made possible by Web 5.0, but the production and interpretation of photographs are less reflective and professional. This issue is made worse by AI and overproduction of images which impairs message comprehension (57% of students). Therefore, given the abundance of flimsy content on social media, ethics in photojournalism are crucial. To conclude, students and future communicators must know the current panorama of photography and photojournalism in the context of Web 5.0.s. Key words: Web 5.0 – overproduction – photography – photojournalism – ethics